Standardized and Experimental Tools to Assess Spatial Cognition in Visually Impaired Children: A Mini-Review - Aprile, Giorgia; Cappagli, Giulia; Morelli, Federica; Gori, Monica; Signorini, Sabrina (Frontiers in Neuroscience, 2020)
The acquisition of spatial cognition is essential for both everyday functioning (e.g. navigation) and more specific goals (e.g. mathematics), therefore being able to assess and monitor spatial cognition from the first years of life would be essential to predict developmental outcomes and timely intervene whenever spatial development is compromised. Several shreds of evidence have indicated that spatial development can be compromised in the case of development with atypical sensory experience such as blindness. Despite the massive importance of spatial abilities for the development of psychomotor competencies across childhood, only a few standardized and experimental methods have been developed to assess them in visually impaired children. In this review, we will give a short overview of current formal (standardized) and informal (experimental) methods to assess spatial cognition in visually impaired children, demonstrating that very few validated tools have been proposed to date. The main contribution of this current work is to highlight the need of ad-hoc studies to create and validate clinical measures to assess spatial cognition in blind individuals and address potential future developments in this area of research.